Level Employabilty Skills Siswa di Sekolah Menengah Kejuruan ditinjau Dari Aspek Kognitif, Afektif, dan Psikomotorik - Amirullah, Muhammad; Aswar, Aswar; Rahayu, Hastriani (Indonesian Journal of School Counseling: Theory, Application, and Development, 2025)
The background of this study is the development of the 21st Century career paradigm that focuses on the development of employability skills. The purpose of this study is to obtain an overview and information about the level of employability skills of students in Vocational High Schools in the review of cognitive, affective, and psychomotor aspects. The research design used in this study is descriptive-analytic with a quantitative approach. Descriptive-analytic research aims to provide factual references regarding the phenomena of the population being studied. The variables used in this study are single variables that only express one idea in a study, namely the variable employability skills of Vocational High School Students. The findings of this study indicate that the level of employability skills of Vocational High School students reviewed from each aspect is in the category of quite capable, which means that most students have understanding, attitudes, and skills that are in the moderate or not optimal category.